Chronic exposure to a pollutant mixture at low doses led to tissue-specific metabolic alterations in male mice fed standard and high-fat high-sucrose diet. (April 2019) - Naville, Danielle; Gaillard, Guillain; Julien, Benoit; Vega, Nathalie; Pinteur, Claudie; Chanon, Stéphanie; Vidal, Hubert; Le Magueresse-Battistoni, Brigitte
Abstract: Excessive consumption of industrialized food and beverages is a major etiologic factor in the epidemics of obesity and associated metabolic diseases because these products are rich in fat and sugar. In addition, they contain food contact materials and environmental pollutants identified as metabolism disrupting chemicals. To evaluate the metabolic impact of these dietary threats (individually or combined), we used a male mouse model of chronic exposure to a mixture of low-dose archetypal food-contaminating chemicals that was added in standard or high-fat, high-sucrose (HFHS) diet. Specifically, the mixture contained bisphenol A, diethylhexylphthalate, 2, 3, 7, 8-tetrachlorodibenzo-p-dioxine and polychlorinated biphenyl 153. Exposure lasted from 5 to 20 weeks of age. Metabolic exploration was conducted setting the basis of candidate gene expression mRNA analyses in liver, jejunum and adipose tissue depots from 20 week-old mice. Strong metabolic deleterious effects of the HFHS diet were demonstrated in line with obesity-associated metabolic features and insulin resistance. Pollutant exposure resulted in significant changes on plasma triglyceride levels and on the expression levels of genes mainly encoding xenobiotic processing in jejunum; estrogen receptors, regulators of lipoprotein lipase and inflammatory markers in jejunum and adipose tissues as well as adipogenesis markers. Importantly, the impact of pollutants was principally evidenced under standard diet. In addition, depending on nutritional conditions and on the metabolic tissue considered, the impact of pollutants could mimic or oppose the HFHS effects. Collectively, the present study extends the cocktail effect concept of a low-dosed pollutant mixture and originally points to tissue-specificity responsiveness especially in jejunum and adipose tissues. Highlights: Low-dosed pollutants trigger metabolic disturbances in postnatally exposed male mice. The mixture of pollutants induced metabolic alterations in a tissue-specific manner. Jejunum is highly sensitive with regards to xenobiotic receptors and lipolysis. Pollutants have a greatest metabolic impact in standard nutritional conditions. Differences in the response to the pollutant mixture were seen between the 2 fat pads.